Bloom : the botanical vernacular in the English novel - King, Amy M. (Amy Mae) (Oxford University Press, 2003)
Starting from the botanical crazes inspired by Linnaeus in the 18th century and exploring the variations it spawned, this study offers a fresh, detailed reading of the courtship novel from Jane Austen to George Eliot and Henry James.